The Role and Impact of Family Psychological Functioning in Improving the Quality and Progress of English Language Learning Skills of Children with Disabilities - Eyvazi, Mojgan (KMAN Counseling & Psychology Nexus, 2023)
This study examines the impact of family psychological functioning on the quality and progress of English language learning skills in children with disabilities, highlighting the role of emotional support and family dynamics in second language acquisition. The study employed a descriptive-correlational design, utilizing a survey method to collect data from 223 parents of children with disabilities aged 8 to 12 years in Tehran. The Family Assessment Device (FAD) was used to measure family psychological functioning, while the TOEFL Primary Test assessed English language learning quality and progress. Pearson correlation analysis was conducted to determine the relationship between the dependent and independent variables, and linear regression analysis was performed to assess the predictive power of family psychological functioning on language learning outcomes. Data analysis was conducted using SPSS-27. The results indicated a significant positive correlation between family psychological functioning and English language learning quality (r = 0.61, p < 0.01) and progress (r = 0.58, p < 0.01). Regression analysis confirmed that family psychological functioning significantly predicted both English learning quality (β = 0.53, p < 0.001) and progress (β = 0.49, p < 0.001). Children from emotionally supportive families demonstrated higher motivation, better vocabulary acquisition, and improved language retention, while those from psychologically distressed families exhibited lower engagement and slower progress in English learning. The study underscores the critical role of family psychological well-being in facilitating second language acquisition among children with disabilities. Emotional support and structured family engagement significantly enhance English language learning quality and progress, suggesting the need for family-centered interventions in language education policies.